Penerapan Audit Laporan Keuangan Bagi Pengelola Koperasi di Kabupaten Madiun - Lestari, Damajanti Sri; Handayani, Alberta Esti (JHP17 (Jurnal Hasil Penelitian), 2019)
Financial Reports are part of the manager's accountability report for an accountingperiod that can be used as material to assess the work of cooperative management. The generalobjective of auditing financial statements is to express an opinion on the fairness of financialstatements, in all material respects, in accordance with accounting principles that are generallyapplicable in Indonesia. Fairness of financial statements is assessed based on assertionscontained in each element presented in the financial statements. The results of the researchconducted on 3 (three) Cooperatives in Madiun showed the following results: KPRI SumberBahagia has provided a fair and complete financial report, even though there are severalaccount names and report formats that must be adjusted to SAK ETAP and Cooperative andSME Ministerial Regulations No. 12 of 2015. KOPWAN Sekar Arum and KOPWAN Rinduhave not provided a fair and complete financial report, because they have never been auditedso that the preparation of financial reports must be adjusted to SAK ETAP and Cooperativeand SME Ministerial Regulation No. 12 of 2015. From the explanation above it can beconcluded that the understanding of the financial report audit at KPRI Sumber Bahagia isgood, while in KOPWAN Sekar Arum and KOPWAN Rindu need to be improved.Keywords: Financial Report Audit, Accountability Report, SAK ETAP